Utilizing the Website Integrated with Social Media as an English Teaching Platform - Titis Wisnu Wijaya; Dwijoko Purbohadi; David Sulistiawan Aditya; Muhammad Miftah (OJS Universitas Muhammadiyah Gresik, 2023)
The sophistication of information and communication technology has penetrated almost all sectors including the education sector. In the past, internet network services could only be accessed by certain groups. However, the current situation is very different. Today, internet services can be accessed by everyone from all social statuses. However, the utilization of the internet network is still far from being optimal. In addition, the use of social media is only for entertainment or a means for playing games. On the other hand, the internet has changed the traditional approach to a modern approach as an example in the realm of pedagogic learning. The implementation of innovative learning media through the use of the internet network makes the learning atmosphere more efficient and interesting. Learning-based websites along with other technology-based tools have shown potential in language teaching. In this case, Teaching English as a Second Language activities are made easier and more interesting through website-based learning. This study aims to utilize the website integrated with social media as an English teaching platform at the Professional English Certificate language institution. With the material in the form of audio-visual, it gives the user unlimited opportunities to repeat the material in parts that have not been mastered well. This naturally corresponds to the learning style of Generation Z; visual, technological, innovation, concrete and critical thinking. According to Technology Pedagogical Content Knowledge, it is necessary to choose the proper use of technology in implementing website-based learning strategies. In practice, the implementation of this community service program is going well. As evidence of the program's success indicators, the community service team distributed questionnaires in assessing the convenience and feasibility of the designed teaching model. The findings demonstrated that 78.5% were in the “Good” category out of 20 samples. The majority of respondents considered that the website integrated with social media with a self-directed learning model was comfortable and feasible to be applied as an English teaching platform.